"On children's games:" A translation of "Lasten Leikeistä". Issue 2 (3rd April 2021) - Selonen, Lauri
ABSTRACT: This translation of the Finnish version of the fourth chapter of the 1916 Barnlek represents one of the earliest occasions of the study of play and games to appear in the Finnish language. The Finnish version which this translation is based on appeared in 1918 under the title "Lasten Leikeistä".